A novel memristive neural network with hidden attractors and its circuitry implementation - Pham, Viet Thanh; Jafari, Sajad; Vaidyanathan, Sundarapandian; Volos, Christos; Wang, Xiong (Science China. Technological sciences, 2016)
Neural networks have been applied in various fields from signal processing, pattern recognition, associative memory to artifi- cial intelligence. Recently, nanoscale memristor has renewed interest in experimental realization of neural network. A neural network with a memristive synaptic weight is studied in this work. Dynamical properties of the proposed neural network are investigated through phase portraits, Poincar6 map, and Lyapunov exponents. Interestingly, the memristive neural network can generate hyperchaotic attractors without the presence of equilibrium points. Moreover, circuital implementation of such memristive neural network is presented to show its feasibility.